Magnetic Supraparticles as Identifiers in Single-Layer Lithium-Ion Battery Pouch Cells - Deuso, Sara Li; Ziegler, Simon; Weber, Daniel; Breuer, Felix; Haddad, Daniel; Müssig, Stephan; Flegler, Andreas; Giffin, Guinevere A.; Mandel, Karl (Chemsuschem, 2024)
The development of effective recycling technologies is essential for the recovery and reuse of the raw materials required for lithium-ion batteries (LIBs). Future recycling processes depend on accessible information, necessitating the implementation of a digital battery passport. The European battery regulation mandates the use of a machine-readable identifier physically attached to the batteries for accessing digital information. Since externally applied optical labels are vulnerable to mechanical damage, technologies for identification without these restrictions could be beneficial. This study demonstrates that magnetic supraparticles (SPs) can be used for contactless identification of lithium nickel manganese cobalt oxide (NMC) battery pouch cells via magnetic particle spectroscopy (MPS) and that multiple pouch cells can be discriminated based on their specific magnetic code. A comparison of three independent model scenarios revealed that the detection of SPs and the impact on cell performance are dependent on the integration location. The results validate the concept of magnetic identification in metallic environments with MPS as an alternative to optical labeling methods. This study provides a foundation for the development of a new selective labeling and identification technology for batteries, with the potential to facilitate recycling and contribute to a more sustainable future.
CRIS-Team Scopus Importer:2024-11-15
Keywords: Battery recycling; Digital product passport; Identification; Magnetic particle spectroscopy; Supraparticles

Reusable and inductively regenerable magnetic activated carbon for removal of organic micropollutants from secondary wastewater effluents - Drenkova-Tuhtan, Asya; Inskeep, Caleb Stewart; Luthardt, Leoni; Deuso, Sara Li; Ballweg, Thomas; Hanselmann, Doris; Béalu, Zoé; Meyer, Carsten; Schug, Benedikt; Steinmetz, Heidrun; Mandel, Karl (Water Research, 2024)
This work introduces a new sustainable alternative of powdered activated carbon (PAC) - magnetically harvestable and reusable after regeneration via inductive heating - for the adsorptive removal of organic micropollutants (OMP) from secondary wastewater effluents. For this purpose, two commercial PACs - lignite “L” (1187 m2/g) and coconut “C”-based (1524 m2/g) - were modified with magnetic iron oxide following two different synthesis approaches: infiltration (“infiltr”) and surface deposition (“depos”) route. The resulting magnetic powdered activated carbons (mPAC) and their precursor PACs were fully characterized before application. The iron oxide content of the modified “L” and “C” samples was ∼30 % and ∼20 %, respectively. Iron oxide gives the PAC beneficial magnetic properties for easy magnetic separation and simultaneously acts as an inductively heatable agent for the carbon regeneration. The infiltrated samples displayed better inductive heating performance and regeneration than their deposited counterparts. Tests with real wastewater showed fast adsorption kinetics of the organic load following the pseudo-second-order kinetic model. Adsorption isotherms were compliant with the Freundlich isotherm model. Sample “L-infiltr” had the best overall adsorption performance throughout 5 reuse cycles when intermediately inductively regenerated (<3 % drop in organics removal per cycle with intermediate regeneration vs. ∼10 % drop per cycle without regeneration). The treated supernatant was additionally tested for 31 representative organic micropollutants and their transformation products (pharmaceuticals, personal care products, industrial chemicals, etc.), where 26 OMPs had consistently high removal (>85 %) throughout 5 cycles with intermediate regeneration and for 28 OMPs the total adsorption efficiency dropped by <5 % after 5 cycle
Keywords: Magnetic induction Magnetite Organic micropollutants Reusable powdered activated carbon Reversible sorption Wastewater effluents